Upaya Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Project Based Learning Dengan Berbantu Google Meet - Ismiyatin Ismiyatin (Universitas Sebelas Maret, 2020)
The objective of this study was to improve student learning outcomes through the application of the Project Based Learning model. The type of research is classroom action research (CAR). The CAR model used was the C. Kemmis & Mc Taggart spiral model which was carried out in 2 cycles. Data collection techniques are test techniques and non-test techniques. The research instrument using questions and observation sheets. The data analysis technique used is comparative descriptive. Based on the results of the study, it was shown that the cognitive domain of mathematics learning outcomes based on the percentage of completeness of pre-cycle, first and second cycle learning outcomes was 40.7%; 70.4%; 88.9%.